Estudo comportamental e efeitos da interação animal-visitante dos felinos do Zoológico de São Paulo - Mata, Emily Perez Guimarães da (2020)
Zoos play the role of conservation, research, environmental education, and recreation centers, and one of their main concerns is the welfare of the animals on display, which can be influenced by factors such as adequate enclosure, balanced feeding, veterinary management and interaction with visiting public. The presence of visitors may influence animal behavior, either positively or negatively. Thus, understanding animal-visitor interaction is extremely helpful in the quest to improve the animals’ well-being and raise public interest, because it may help the species' conservation. Therefore, the general objective of this work was to analyze the crowd’s effect on the behavior of the cats at the São Paulo Zoo, and how the behavior of the cats affects the public's interest. 20 hours of behavioral observations were made for each species - Herpailurus yagouaroundi, Puma concolor, Panthera onca, Panthera leo, and Panthera tigris tigris - via focal animal sampling for enclosures with only one individual and scan sampling for enclosures with multiple animals. The recorded behaviors were then correlated to the visitors' behavior, age group, and length of stay in front of the venues. Furthermore, modifications were made to the structural and environmental elements of the H. yagouaroundi enclosure to verify the effect of these changes on the activity of the animals and the perception and interest of the public, and, following, new behavioral observations were made. The results showed that cats, in general, exhibited behaviors related to rest, such as lying down or remaining inactive in structures. The stereotyped behavior, pacing, was observed more frequently for the jaguar. As for other factors that could influence the cat’s behavior, such as the age range of the visitors and the time of the visit, they showed no effect, however, the pacing events occurred mainly during mornings. After the changes were made in the H. yagouaroundi enclosure, there was a reduction in the inactive and stereotyped behaviors of the species. Therefore, the enrichment of ex situ environments can be considered an important tool for zoos and institutions with animals under human care to promote the welfare of the animals, providing more complex environments so their behavioral repertoire can approach what is observed in their natural habitat. Also, the setting of the enclosures may promote greater attractiveness to the visiting public and consequently deeper knowledge, affection, and respect for the animals in captivity.